2012
DOI: 10.1128/jcm.01045-12
|View full text |Cite
|
Sign up to set email alerts
|

Formic Acid-Based Direct, On-Plate Testing of Yeast and Corynebacterium Species by Bruker Biotyper Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: An on-plate testing method using formic acid was evaluated on the Bruker Biotyper matrix-assisted laser desorption ionizationtime of flight (MALDI-TOF) mass spectrometry system using 90 yeast and 78 Corynebacterium species isolates, and 95.6 and 81.1% of yeast and 96.1 and 92.3% of Corynebacterium isolates were correctly identified to the genus and species levels, respectively. The on-plate method using formic acid yielded identification percentages similar to those for the conventional but more laborious tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 7 publications
(20 reference statements)
6
86
0
9
Order By: Relevance
“…The use of matrixassisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for the rapid identification of clinical yeast and mycobacterial isolates has been evaluated in some studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, there has been a limited number of direct comparison studies focusing on the performance of the two MALDI-TOF systems to rapidly identify yeast and mycobacterial clinical isolates (26)(27)(28).…”
mentioning
confidence: 99%
“…The use of matrixassisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for the rapid identification of clinical yeast and mycobacterial isolates has been evaluated in some studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, there has been a limited number of direct comparison studies focusing on the performance of the two MALDI-TOF systems to rapidly identify yeast and mycobacterial clinical isolates (26)(27)(28).…”
mentioning
confidence: 99%
“…Similar identification rates were reported for Corynebacterium spp. and anaerobic bacteria when on-target formic acid preparation and extraction were compared (19,24). An alternative preparation method with on-target ethanol treatment was described by Farfour et al (25), who analyzed a large collection of GPR using the Andromas system and reported accurate species identification.…”
mentioning
confidence: 99%
“…An alternative preparation method with on-target ethanol treatment was described by Farfour et al (25), who analyzed a large collection of GPR using the Andromas system and reported accurate species identification. Few studies have systematically compared different sample preparation methods for the identification of GPR with MALDI-TOF MS (13,24,26).…”
mentioning
confidence: 99%
“…Mayaların MALDI-TOF MS ile identifikasyonu öncesinde yaklaşık 25 dakika süren bir ekstraksiyon aşaması gerçekleştirilmesi gerekli olmakla birlikte, bazı araştırmacılar buna alternatif olan ve daha kısa süren yöntemler geliştirdiklerini bildirmişlerdir (13)(14)(15)(16)(17)(18)(19) .…”
Section: Discussionunclassified